(untitled) (New York, 1992)
This handbook emphasizes in-depth presentation of environmental pollution sources, waste characteristics, control technologies, mangement strategies, facility innovations, process alternatives, costs, case histories, effluent standards, and future trends for each industrial or commercial operation.
Keywords: Factory and trade waste; Management